2016
DOI: 10.1021/acsami.6b08610
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Enhancement of Graphene Oxide/Silk Nanocomposite Membranes: Increasing Toughness, Strength, and Young’s modulus via Annealing of Interfacial Structures

Abstract: We demonstrate that stronger and more robust nacre-like laminated GO (graphene oxide)/SF (silk fibroin) nanocomposite membranes can be obtained by selectively tailoring the interfacial interactions between "bricks"-GO sheets and "mortar"-silk interlayers via controlled water vapor annealing. This facial annealing process relaxes the secondary structure of silk backbones confined between flexible GO sheets. The increased mobility leads to a significant increase in ultimate strength (by up to 41%), Young's modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 78 publications
0
102
0
Order By: Relevance
“…[51,58,90] Figure 2 shows that in the past decade, an increasing research effort has been made to improve the mechanical properties of graphene-based nanocomposites by various interfacial www.advmatinterfaces.de modifications. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, [81,[115][116][117][118] π-π interaction, [119][120][121] and covalent bonding. Inspired by nacre, a vast variety of highperformance GO-based nanocomposites and their reduced counterparts, including 1D fibers, 2D films, and 3D bulk materials, have been successfully constructed by interfacial crosslinking and building block toughening.…”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[51,58,90] Figure 2 shows that in the past decade, an increasing research effort has been made to improve the mechanical properties of graphene-based nanocomposites by various interfacial www.advmatinterfaces.de modifications. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, [81,[115][116][117][118] π-π interaction, [119][120][121] and covalent bonding. Inspired by nacre, a vast variety of highperformance GO-based nanocomposites and their reduced counterparts, including 1D fibers, 2D films, and 3D bulk materials, have been successfully constructed by interfacial crosslinking and building block toughening.…”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 99%
“…Various molecules, including small solvent molecules, [104,145,146] linear polymers, [102,104,110,113,[147][148][149] branched polymers, [111] and biomacromolecules, [96,105,106,114,150] could be used to construct hydrogen bonding between adjacent GO nanosheets. Various molecules, including small solvent molecules, [104,145,146] linear polymers, [102,104,110,113,[147][148][149] branched polymers, [111] and biomacromolecules, [96,105,106,114,150] could be used to construct hydrogen bonding between adjacent GO nanosheets.…”
Section: 1 Hydrogen Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing concentration of graphene‐family materials, the content of silk II structure (β‐sheet) in composites increased, without any evidence of a downward trend ,. The mechanical properties of the composite materials were also increased significantly at higher concentrations of graphene‐family materials within the specified range ,. A recent study showed that the secondary structure of SF chains adsorbed on GO was also highly dependent on the pH level, leading to different changes in the composites’ properties .…”
Section: Combined Application Of Graphene‐family Materials and Sfmentioning
confidence: 98%
“…Much work has also focused on the assembly of nanocomposites, whereby GO acts as 2D “bricks” bound by 1D polymeric binders to yield nacre‐like structures designed for superior mechanical properties, including extreme tensile strength (526.7 MPa in GO–chitosan), Young's modulus, toughness (13.9 MJ m −3 reduced graphene oxide–silk fibroin, GO–SF), and stretchability (up to 10.1% in GO–polyvinyl alcohol) . Synergistic effects arise from confined networks of intermolecular interactions to produce materials with superior mechanical properties in composites otherwise comprised of soft constituent components . However, the investigation of layered graphene composites has been largely confined to structural applications .…”
Section: Introductionmentioning
confidence: 99%